A "quota silo" or positive equality reach? The equality impact of gender quotas on corporate boards in Norway. (27th April 2020) - Seierstad, Cathrine; Healy, Geraldine; Sønju Le Bruyn Goldeng, Eskil; Fjellvær, Hilde
Abstract: 10 years after its implementation, we explore the equality reach of the 40% Norwegian gender quota regulation for boards of public limited companies (PLCs) using a multi‐strategy approach (administrative data and interviews with women directors) to capture interrelated macro and meso changes. We employ Acker's (2006) inequality regimes as our analytical framework, augmented by the "equality reach" concept. We found strong compliance with the 40% Quota. However, there was little evidence of voluntary spillover to limited companies as envisaged by Quota proponents; instead Quota coverage reduced as some PLCs changed status to avoid the Quota requirement. We reveal that positive equality reach in one of the most equal countries in the world is confined to a PLC "quota silo, " which has shrunk over the life of the Quota. Moreover, we suggest that PLC high levels of compliance may be a defensive strategy seen as necessary in the regulatory/high sanction context of the Quota. We demonstrate the need for further political and organisational interventions to improve equality reach beyond the quota silo. We also show the value of the equality reach concept for research on equality interventions and warn of the dangers of an intervention leading to an equality silo.